Aerosol processing: a wind of innovation in the field of advanced heterogeneous catalysts - Debecker, Damien P; Le Bras, Solène; Boissière, Cédric; Chaumonnot, Alexandra; Sanchez, Clément (Chemical Society reviews, 2018)
Aerosol processing is long known and implemented industrially to obtain various types of divided materials and nanomaterials. The atomisation of a liquid solution or suspension produces a mist of aerosol droplets which can then be transformed via a diversity of processes including spray-drying, spray pyrolysis, flame spray pyrolysis, thermal decomposition, micronisation, gas atomisation, etc. The attractive technical features of these aerosol processes make them highly interesting for the continuous, large scale, and tailored production of heterogeneous catalysts. Indeed, during aerosol processing, each liquid droplet undergoes well-controlled physical and chemical transformations, allowing for example to dry and aggregate pre-existing solid particles or to synthesise new micro- or nanoparticles from mixtures of molecular or colloidal precursors. In the last two decades, more advanced reactive aerosol processes have emerged as innovative means to synthesise tailored-made nanomaterials with tunable surface properties, textures, compositions, etc. In particular, the "aerosol-assisted sol-gel" process (AASG) has demonstrated tremendous potential for the preparation of high-performance heterogeneous catalysts. The method is mainly based on the low-cost, scalable, and environmentally benign sol-gel chemistry process, often coupled with the evaporation-induced self-assembly (EISA) concept. It allows producing micronic or submicronic, inorganic or hybrid organic-inorganic particles bearing tuneable and calibrated porous structures at different scales. In addition, pre-formed nanoparticles can be easily incorporated or formed in a "one-pot" bottom-up approach within the porous inorganic or hybrid spheres produced by such spray drying method. Thus, multifunctional catalysts with tailored catalytic activities can be prepared in a relatively simple way. This account is an overview of aerosol processed heterogeneous catalysts which demonstrated interesting performance in various relevant chemical reactions like isomerisation, hydrogenation, olefin metathesis, pollutant total oxidation, selective oxidation, CO2 methanation, etc. A short survey of patents and industrial applications is also presented. Our objective is to demonstrate the tremendous possibilities offered by the coupling between bottom up synthesis routes and these aerosol processing technologies which will most probably represent a major route of innovation in the mushrooming field of catalyst preparation research.